Telaah Wacana Imperialisme Budaya Tokusatsu Jepang Melalui Iklan Marjan Versi Wayang Golek - Halla Puspita Yuri; Hartanto Jahja; Rewindinar Rewindinar; Yuri Alfrin Aladdin; Rustono Farady Marta (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2020)
Technological progress in the field of robotics is something that is idolized in homeland. Robotics often appears along with the tendency of the Japan which is popular with futuristic technology. Indonesia is affected by Japan's tokusatsu shows because we ourselves are still lagging behind in the fields of technology and culture. The era of Japanese colonialism towards Indonesia over the past 3.5 years seemed to reincarnate into cultural imperialism, one of which can be listened to through the Marjan syrup ads version of "Wayang (puppet) Golek Cepot Dawala". Researchers used Teun A. Van Dijk's critical discourse analysis method that discusses microstructure, macro structure, and social context based on visual elements of images and sounds. In the structure of the text, researchers found a friction between traditional Indonesian culture and modern Japanese robotics and a shift in traditional culture that is now beginning to be replaced by modern culture among young people. Cognition and the social context that appears in ads portraying Indonesian traditional culture could not survive if it did not adopt modern Japanese robotic culture, even if the meaning of the traditional culture changes considerably and further accentuates the modern culture.